2012
DOI: 10.1177/1933719112446080
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol in the Pathophysiology of Endometriosis: Focus on Angiogenesis and Therapeutic Potential

Abstract: Endometriosis is a common condition among women of childbearing potential in which ectopic endometrial tissue is found outside the uterine cavity. Neoangiogenesis plays a major role in the development of endometriotic implants. Some evidence suggests that a disorder in the balance of proangiogenic and antiangiogenic factors that favors the former is induced by local hypoxia and is mediated by the hypoxia-inducible factor-vascular endothelium growth factor pathway could partially explain the development of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 117 publications
0
16
0
Order By: Relevance
“…For many other factors it remains unclear whether they are the cause or the consequence of endometriosis. Pelvic endometriosis is associated with a low-grade inflammation of the peritoneal cavity with higher concentrations of activated macrophages and thus with higher concentrations of the many different cytokines (68-72) and angiogenic factors (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The many immunologic disturbances were recently reviewed (92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Development Of (Deep) Endometriosis: Players and Mechanismsmentioning
confidence: 99%
“…For many other factors it remains unclear whether they are the cause or the consequence of endometriosis. Pelvic endometriosis is associated with a low-grade inflammation of the peritoneal cavity with higher concentrations of activated macrophages and thus with higher concentrations of the many different cytokines (68-72) and angiogenic factors (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The many immunologic disturbances were recently reviewed (92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Development Of (Deep) Endometriosis: Players and Mechanismsmentioning
confidence: 99%
“…Changes in estradiol homeostasis have been locally observed in endometriosis. A balance was observed between local 2-methoxyestradiol production and angiogenesis, which could promote the development of endometriotic lesions [147]. …”
Section: Immune Disturbance Of the Peritoneal Microenvironmentmentioning
confidence: 99%
“…1a), the endogenous metabolite of 17$-estradiol, have been documented extensively during the last two decades. As noted in reviews and research articles referring to the status of 2ME as a drug candidate, [1][2][3][4] it has been administered orally in Phase I/II clinical trials for a range of diseases (e.g., ovarian, brain, breast, and prostate cancers) and found to display relatively low toxicity. However, the low aqueous solubility of 2ME and its extensive metabolism (via glucuronidation in particular) have been shown to result in low bioavailability (ß1.5%), which has limited its development, 3,5 and consequently prompted efforts to create active analogs and derivatives by chemical elaboration of the 2ME scaffold (see below).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent study using mouse models, it was shown that 2ME shows acute anti-inflammatory activity that cannot be attributed to its known antiproliferative/antiangiogenic activities. 6 2ME has also been identified as a promising new candidate for the treatment of endometriosis 4 and its possible future role in the context of more general disorders of female reproductive tissues has been reviewed very recently. 7 Combined use of 2ME and conventional chemotherapeutic agents (e.g., gemcitabine and cisplatin) has been shown to result in enhanced growth inhibition of human pancreatic cancer cells, 8 prompting the suggestion that clinical trials of such combinations are warranted.…”
Section: Introductionmentioning
confidence: 99%